Donor Darah dengan tema Setetes Darah dapat Menyelamatkan Satu Nyawa Saudara Kita - Haryati Sahrir; Ricky Zainuddin; Rianti Rumbia (Lembaga Pengembangan Kinerja Dosen, 2022)
Blood is an important component for the human body, therefore blood supplies at the Indonesian Red Cross must be maintained. After the Covid-19 pandemic that hit Indonesia, the number of blood supplies at the Indonesian Red Cross decreased. Seeing this condition, lecturers and students from the D3 Midwifery Study Program at the Makassar College of Health Sciences initiated community service activities in the form of blood donations with the aim of attracting public interest and becoming agents of change for the Blood Donation movement to increase the number of blood bag supplies at PMI Makassar City, an effort humanity to help others and a concrete manifestation of community service as one of the Tri Dharma of Higher Education. The activity was carried out on July 20 2022 at Mbuuk Coffee and Resto, Makassar City, while still implementing health protocols and 3M principles. There were 85 participants who registered, and 58 participants met the requirements as donors. The amount of blood collected was 58 bags. Overall, the event ran smoothly and orderly and was expected.